ON THE REACTION OF MARINE FISHES IN INTERRUPTED A.C OF 50 Hz - BISWAS, K P (Fishery Technology, 2025)
The reactions of marine fishes i-n interrupted A. C. off uniform electrical fie]d and constant current dt"nsity have been studied in order to determine the optimum effective periods of shock :for narcosis and fixation. Higher effective periods were required with gradual decrease in potential difference between head and tail, which in turn depended on the length of fish and its position in electrical field. The body voltage of fish varied directly with the length and inversely with the rise of angle between their body axis and field lines. The fish subjected to higher effective pe:riod took longer time for recovery from narcosis. The effect of impulse current was manifested by increased rate of giH movements in P!atax tefora, Haetodon ollaris, Crysophus burda, Siganus vermiculatus and Scolopsis leucotaenia, and lowered rate of movements in others when subjected to different effective periods inespective